Pengaruh Layanan Perpustakaan Terhadap KKepuasan Pemustaka di Perpustakaan Universitas Negeri Padang - Zaharani, Reihan; Primadesi, Yona (Ilmu Informasi Perpustakaan dan Kearsipan, 2014)
This article discusses the influence of library services to the satisfaction of the visitors at the Library of the State University of Padang. This study aims to determine the effect of library services to the satisfaction of the visitors at the Library of the State University Padang. Data collected through questionnaires and observation. Â Based on analyzing the data, it was concluded the following matters: (1) services in the Library of the State University of Padang less satisfactory, because it appears that the existing services at the Library of the State University of Padang not provide optimal service; (2) State University of Padang library atmosphere is quite comfortable for the visitors; (3) State University of Padang less librarian guiding the visitors during a visit to the library; (4) Library, State University of Padang quite a positive impact on the visitors. Keywords: influence; service; satisfaction; user library